Evaluasi Dan Perancangan User Interface Untuk Meningkatkan User Experience Menggunakan Metode Human Centered Design Dan Heuristic Evaluation Pada Aplikasi EzyPay - Dhika Rozqi Anggitama; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-Payment is a payment system that uses internet facility as a medium of intermediary. Nowadays many start-up business that facilitate seller and giving a guaranteed safety transaction. Many activities that can be done easily via mobile devices, including payment activites. EzyPay is an online payment application to help people get payment transactions and bill payments. EzyPay is downloaded more than 10,000 times by users via Playstore. Rating obtained by EzyPay application on Playstore reached 3.9 for version 1.0.24. The common problems found are, the designs and the elements in the EzyPay application are inconsistent so it complicate the user. To improve and finding the usability problem specifically needed the process of User Interface design with a method of Heuristic Evaluation (HE). This evaluation and design in order to increase the number of user that downloaded, used, also to increase the ease when using EzyPay application. Problems found in the evaluation of first phase found 26 problems with 5 similar problems. In the second phase of evaluation 2 found a fewer problem that is 8 problems. The problems in the first phase of evaluation were not found in the second phase of evaluation. Therefore, the problems in the first phase evaluation have been successfully improved. This research to produce a problems analytical and giving an appropriate recommendation for developer to improvement also high-fidelity prototype as a solution idea.